Candace Bowen: capstone - Bowen, Candace, artist (Colorado State University. Libraries, 2015)
The artist's statement: My work revolves around ideas of femininity and how these ideas are affected by the threats women currently face. With my age and student status, I am part of one of the largest target groups for sexual assault; which makes these threats closer than they have been or will be in my lifetime. I have experienced this fear and know how consuming it can become. Going out to bars, agreeing to a blind date, walking across campus at night, or even walking into your own home alone can result in a horrifying situation that can forever change a woman's life. With this in mind, I try to create paintings that contain the essence of femininity combined with the real fear women face in everyday situations. In my paintings I use real stories and accounts of fearful situations to create my setup, combining everyday "feminine" objects and things associated with innocence; makeup, perfume, angels, stuffed animals, jewelry, etc., alongside objects of self-defense. Often these scenes take place in an intimate setting, for example the bedroom of the storyteller. In doing so, I try to bring the sense of constant worry and fear women face, even when in the comfort of their own homes. By devoting the time to convey these images in a very realistic way, I attempt to give these items the respect, dedication, and commitment that demonstrates the importance of this issue. The fact that women must live their lives in this way is absurd. This topic is not something I feel I can just photograph or document; it has to be given the time I take to paint it to emphasize its significance. I hope that by dedicating my time, passion, and artwork to this topic, I will bring about the discussion and importance it so desperately needs to encourage change.
Colorado State University Art and Art History Department capstone project.
Capstone contains the artist's statement, a list of works, and images of works.
Keywords: painting